Determinasi Kepatuhan Pajak Digital Melalui Kepercayaan dan Manfaat Sistem Coretax: Peran Literasi Digital - Nurhapsari, Risma; Titik Rianawati; Olivia Rahmala Iwan; Sabtarini Kusumaningsih; Galuh Aninditiyah; Hesiya May Ghaisani (IPM2KPE, 2026)
This study aims to analyze the determinants of digital tax compliance through trust in and the benefits of the Coretax system, with digital literacy as a moderating variable. The research method used was a mixed methods approach, combining a quantitative survey of 150 taxpayer Coretax users and semi-structured qualitative interviews to gain an in-depth understanding of user experiences. The results indicate that trust in the Coretax system, perceived benefits of the system, and digital literacy significantly influence digital tax compliance. However, digital literacy does not moderate the effect of trust in or benefits of the system on digital tax compliance. The conclusion of this study confirms that improving system quality, perceived benefits, and taxpayer digital competence are key to driving the success of digital tax transformation in Indonesia. Keywords: Digital Tax Compliance, System Trust, System Benefits, Digital Literacy